Early drug-induced hepatotoxicity in newly diagnosed HIV-positive patients on ARV therapy: A retrospective follow-up study of liver function profiles - Chandra, Lukman Ade; Subronto, Yanri Wijayanti; Thobari, Jarir At (Indonesian Journal of Pharmacology and Therapy, 2023)
Antiretroviral therapy (ART) is a primary therapeutic modality for managing individuals with Human Immunodeficiency Virus (HIV) infection, and its efficacy has been established. However, the safety profiles of ART need to be continually monitored, including early elevated liver function test (LFT) after antiretroviral (ARV) initiation. This study aimed to assess the incidence of abnormal LFT among HIV-positive patients receiving initial ARV and to identify factors associated with abnormal LFT. A retrospective cohort study without a control group summarised medical records from Dr Sardjito General Hospital, Yogyakarta between January 2014 and December 2021. The study subjects were adult HIV patients taking their first ARV and underwent follow-up visits for at least two weeks. Study outcomes were LFT levels, abnormal LFT, and factors associated with abnormal LFT during follow-up visits at 2 wk, 6 mo, and 12 mo. Univariate and multivariate analyses will be performed with a significance level of p<0.05. A total of 137 subjects with 203 visits were retrieved from medical records. The subjects' mean age was 33.4 years, predominantly male, younger, unmarried, in the early stage of HIV infection, and without comorbidities. The findings showed a significant increase in alanine transaminase (ALT) at all three follow-up visits: 2 wk (p=0.02), 6 mo (p=0.003), 12 mo (p=0.001) and an increase in aspartate aminotransferase (AST) after 6 mo (p=0.007) and 12 mo (p=0.04). Abnormal LFT levels (AST and/or ALT) were observed in 23.4% of patients after a normal baseline, with ALT increase being more common. Furthermore, homosexuality was identified as a significant independent factor associated with abnormal LFT (AOR=3.1; 95% CI 1.27-7.51; p=0.01). The findings indicate exceptionally elevated LFT levels and the occurrence of abnormal LFTs among HIV-positive patients initiating ARVs. The increase in abnormal LFTs was significantly associated with patients identifying as homosexual, where hepatitis co-infection may be a contributing factor. The limited study design and measured variables warrant further investigation.